Applewhites coast to coast - Tolan, Stephanie S.; Tolan, R. J. (Harper, 2017)
Thirteen-year-old E.D. Applewhite, still reeling from her bewildering kiss with former bad boy Jake, embarks on a cross-country road trip in a wildly painted school bus with her eccentric, highly creative family, as they compete in an art educational quest for a big cash prize.